Risk Factors for Systemic Reduced Bone Mineral Density in Premenopausal Female Patients with Early Untreated Rheumatoid Arthritis - Ahmed, Hamada S.; Farrag, Sherif E.; Okasha, Amr E.; Othman, Gamal; Shady, Ibrahim (Aktuelle Rheumatologie, 2018)
Background Systemic osteoporosis (OP) is evident among patients with early rheumatoid arthritis (ERA). This study aimed to investigate the OP risk factors in patients with ERA and who was treatment-naïve at inclusion.Subjects and Methods Systemic bone mineral density (BMD) of the lumbar spine (LS), femoral neck (FN) and total hip (TH) was measured in 135 treatment-naïve premenopausal females with early Rheumatoid Arthritis (ERA). For all patients, demographic data, vitamin D status, and the specific parameters of the disease, including disease activity, serum levels of rheumatoid factor and anti-citrullinated protein antibodies (ACPA) were evaluated.Results T score was<−1.0 in the LS in 16.2%, in the FN in 22.2% and in the TH in 23.7%. Among our patients, 29.6% had below normal T score at any site. Demographic characteristics, RA duration, diseases activity did not significantly impact BMD. However, patients with decreased BMD were more prevalent ACPA- and rheumatoid factor (RF)-positive than patients with normal BMD. Also, high titer ACPA or RF is associated with more marked reduction in BMD. In regression analysis, after adjustment for possible confounders, patient stratification according to ACPA status and RF status (into negative, low-positive and high positive) still a significant independent variable associated with lower BMD values.Conclusion Presence of ACPA or RF is associated with increased risk for development of reduced systemic BMD from very early stage of rheumatoid arthritis. Furthermore, this risk increases more with higher levels of ACPA or RF. Measurement of BMD should be performed for ACPA- or RF-positive patients with early RA.
Keywords: Frühe rheumatoide Arthritis; Osteoporose; Rheumafaktor; Antikörper gegen citrullinierte Proteine